Pre-Planting Hardening-Induced Variability in Yield Attributes and Yield of Inbreed and Hybrid Rice - Masrufa, Sadia; Rahman, Anisur; Hasanuzzaman, Md; Anee, Taufika Islam; Ali, Md Hazrat; Hasanuzzaman, Mirza (Bangladesh Agronomy Journal, 2016)
Short term hardening before transplanting may enhance the defence mechanism of rice seedlings against any stress during their establishment and contribute d to enhanced growth and yield. Thus, this study was conducted involving one local inbred (Pajam), one popular high yielding (BRRI dhan53) and one hybrid (BRRI hybrid dhan4) rice variety. The experiment was laid out in randomized complete block design with two factors. Seedlings were transplanted directly to the main field as a control treatment and/or subjected to four different hardenings like seedlings storage in shade, open field under sunlight, float in water and cold air in refrigerator before transplantation. Hybrid variety out yielded both the local and inbred varieties due to their highest effective tillers, longer panicle length and 1000-grain weight. Pre-hardening of seedlings in open field under sunlight conditions enhanced the yield attributes and ultimate yield of rice compare to others. The best combination was pre-hardening seedlings in open field conditions with hybrid cultivar regarding to the yield attributes and final yields. It is suggested that hybrid variety and prehardening of seedlings before transplantation to the main field could be increase the rice yield productions Bangladesh Agron. J. 2016, 19(1): 87-97